2020
DOI: 10.1016/j.tws.2020.106871
|View full text |Cite
|
Sign up to set email alerts
|

Failure and detachment path of impulsively loaded plates

Abstract: The deformation and detachment path of simply-supported and fully clamped mild steel quadrangular plates subjected to impulsive blast loads are investigated numerically. A comprehensive failure model that incorporates two competing mechanisms of damage due to ductile and shear failure is employed to simulate the progression of tearing within the plate. The stress triaxiality dependent Modified Mohr-Coulomb (MMC) fracture criterion is implemented in a finite element model, and experimental tensile and shear tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Notice that the numerical prediction of failure behaviour is dependent upon the value of failure strain, i.e. a greater value of ¯ f would delay the onset of fracture as shown previously in the work of [9,43].…”
Section: Failure Criterionmentioning
confidence: 65%
See 2 more Smart Citations
“…Notice that the numerical prediction of failure behaviour is dependent upon the value of failure strain, i.e. a greater value of ¯ f would delay the onset of fracture as shown previously in the work of [9,43].…”
Section: Failure Criterionmentioning
confidence: 65%
“…5; whereas the results predicted using a 16 × 16 mm 2 mesh indicates a different fracture behaviour. It is hardly surprising that the predictions for damage evolution is mesh-dependent -due to the stress singularities at the sharp corner of the square holes -as was previously noted in [9,[43][44][45]. Using a different failure criterion based on critical plastic work, Aune et al [2], too, found that the predicted damage evolution of the air-blast loaded ductile plate with square holes also depends upon the mesh size.…”
Section: Mesh Sensitivity Studymentioning
confidence: 81%
See 1 more Smart Citation